2022
DOI: 10.1109/access.2022.3170910
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of Transmitted Signal Distortion Caused by Power Allocation in Inter-Cell Interference Coordination Techniques for LTE/LTE-A and 5G Systems

Abstract: Error vector magnitude (EVM) and out-of-band emissions are key metrics for evaluating in-band and out-band distortions introduced by all potential non-idealities in the transmitters of wireless systems. As EVM is a measure of the quality of the modulated signal/symbols, LTE/LTE-A and 5G systems specify mandatory EVM requirements in transmission for each modulation scheme. This paper analyzes the influence of the mandatory satisfaction of EVM requirements on the design of radio resource management strategies (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Recent research and development in the area of wireless communications using software-defined radio (SDR) platforms have been primordial in testing novel algorithms and network architectures allowing a faster evolution and deployment of the proofs-of-concept in the 5G communication networks [32], [33]. Furthermore, our research team has demonstrated the viability of employing the SDR together with Matlab TM software in the cooperative 5G network implementation [34].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent research and development in the area of wireless communications using software-defined radio (SDR) platforms have been primordial in testing novel algorithms and network architectures allowing a faster evolution and deployment of the proofs-of-concept in the 5G communication networks [32], [33]. Furthermore, our research team has demonstrated the viability of employing the SDR together with Matlab TM software in the cooperative 5G network implementation [34].…”
Section: Introductionmentioning
confidence: 98%
“…It is worthwhile to mention the amount of research involving theoretical aspects of the design of IAB architectures [24], [26], [27]. Besides, several works have studied the link-level simulation of the mmWave backhaul network and the hardware implementation still constitutes a significant challenge [28], [31], [32]. It should be highlighted that the theoretical implementations and link-level simulations are really an important way for studying algorithms and architectures.…”
Section: Introductionmentioning
confidence: 99%
“…In Reference [2], the signal distortion due to power allocation in various FFR schemes was studied. The joint optimization of FFR and the modern cellular technique, particularly Dynamic Time-Divison Duplex, was investigated [3].…”
Section: Introductionmentioning
confidence: 99%